DAMPAK LIBERALISASI TARIF TERHADAP BEBERAPA PRODUK EKSPOR UTAMA INDONESIA - Adrian D. Lubis (Buletin Ilmiah Litbang Perdagangan, 2009)
Tariff liberalization for Indonesia and European Union (EU) will increase competitiveness, and national welfare for both countries. Liberalization also will increase Indonesia labor demand, but will not significanly increase Indonesia trade value. This study also found that Indonesia private sector need time to adjust with liberal condition. However, it recommends Indonesia to choose long term liberalization, and need more cooperation, and ecofriendly.  All of this proposal will increase Indonesia capability to penetrate EU market.